The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s12098-009-0058-5
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine responsive megaloblastic anemia syndrome

Abstract: Thiamine responsive megaloblastic anemia syndrome (TRMA) is a clinical triad characterized by thiamine-responsive anemia, diabetes mellitus and sensorineural deafness. We report a 4-year-old girl with TRMA whose anemia improved following administration of thiamine and this case report sensitizes the early diagnosis and treatment with thiamine in children presenting with anemia, diabetes and deafness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…Our case also supports the reversibility of diabetes mellitus. In conclusion we report first case of TRMA from Kashmir valley, third from India[1920] and incidentally the first association of TRMA with PDA in the world. This case report stresses the need toward early diagnosis and treatment with thiamine in children presenting with anemia, diabete,s and deafness.…”
Section: Discussionmentioning
confidence: 89%
“…Our case also supports the reversibility of diabetes mellitus. In conclusion we report first case of TRMA from Kashmir valley, third from India[1920] and incidentally the first association of TRMA with PDA in the world. This case report stresses the need toward early diagnosis and treatment with thiamine in children presenting with anemia, diabete,s and deafness.…”
Section: Discussionmentioning
confidence: 89%
“…Bone marrow shows megaloblastosis affecting the erythroid, myeloid and megakaryocyte lines. The classical haematological feature is megaloblastic anaemia with erythroblasts, which is often complicated with ringed sideroblasts, thrombocytopenia and neutropenia 10. Boros et al have shown that defective nucleic acid synthesis through impaired transketolase catalysis is the underlying biochemical disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…We read with interest the case report on Thiamineresponsive megaloblastic anemia (TRMA) [1]. We report our experience with three children with TRMA in two south Indian families.…”
Section: Sirmentioning
confidence: 99%
“…
Sir,We read with interest the case report on Thiamineresponsive megaloblastic anemia (TRMA) [1]. We report our experience with three children with TRMA in two south Indian families.

Case 1 A 12-month-old boy, born to a nonconsanguineous Hindu couple was brought for evaluation of recurrent severe pallor, skin bleeds and hearing impairment.

…”
mentioning
confidence: 99%